Strategi Peningkatan Kualitas, Inovasi Rasa, Dan Pemasaran Keripik Pisang UMKM Di Desa Lantasan Baru - Sakinah Siregar; Sintia Yesepa; Tanzil Hafiz; Tiodara Anggie Sihaloho; Titi Lestia; Ulfa Beutari; Lia Afriyanti Nasution (LPPI UMN AL WASHLIYAH, 2025)
Banana chips are a local food product with high economic potential for rural communities. This program aims to improve product quality, develop flavor innovation, and expand marketing strategies for MSMEs producing banana chips in Lantasan Baru Village, Patumbak District, Deli Serdang Regency. The method used was a participatory approach involving technical training, new flavor development, and digital marketing outreach. The results showed significant improvements in three main aspects: enhanced product quality through better raw materials and processing techniques; diversification into chocolate, matcha, and tiramisu flavors; and expanded market reach via social media and e-commerce platforms. The program also increased the partners’ knowledge and skills, particularly Sumini,, in managing village-based enterprises. In conclusion, this activity successfully empowered rural MSMEs through sustainable improvements in product quality and marketing.